The Role of Staphylococcus Aureus in Chronic Infections: Mechanisms and Treatment Strategies - Abdul Aziz, Bahaa Sufyan Hamid; hamed, Sura Numan Sarhan; Abdullah, Omar Talal Arabi; Saleh Alwan, Sabrin Hameed; Madab, Murad Mudher (American Journal of Biology and Natural Sciences, 2024)
Due to increasing antibiotic resistance, huge efforts are being put into the understanding and biotechnological design of extremely specific, novel antimycotics and their application to staphylococcal infections in various body compartments. In chronic infections, antibiotics are often ineffective. In joints, the bacteria induce synovitis and produce toxins that cause joint destruction. For osteomyelitis, standard treatment involves extensive surgery and prolonged use of antibiotics. Non-specific immune stimuli might activate the immune system to better outnumber the bacterial load. Cyclodextrins can eliminate more fast-growing, small colony variants of bacteria that reside in the osteoblasts and that might be prone to give a recurrent infection. It shows how specialized therapies are relevant, but also insists on a better understanding of the niches that shelter the bacteria and on effective ways to eliminate the organism and lead to a complete cure.